New version of lloyd’s open form standard salvage agreement: LOF 2020 - ÇAKAN ÇAVUŞ, CANSU (NOVA Science Publishers Inc., 2023)
Since its inception, the Lloyd’s Open Form (LOF), the most favoured standard form of agreement for salvage operations, has been revised several times. The most recent amendments made in 2020 are particularly welcome as they have the potential to expedite the arbitration process considerably and facilitate the provision of security. The purpose of this chapter is to elaborate on and explain this latest amendment. In that vein, the evolution of the LOF is first presented briefly as background following which the latest amendments to the LOF text are reviewed in contextual detail. The various texts of the LOF from the past to the present are evaluated and the key changes introduced in the 2020 version are critically examined which constitutes the main aspect of the text. The relatively minor changes are then mentioned. Finally, a summary of the revisions is presented together with the final remarks of the author.
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Özel Hukuk; Social Sciences and Humanities; Law; Private Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities